2011
DOI: 10.1016/j.jmb.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Kinetics of Interrupted Polyglutamine Peptides

Abstract: Abnormally expanded polyglutamine domains are associated with at least nine neurodegenerative diseases, including Huntington’s disease. Expansion of the glutamine region facilitates aggregation of the impacted protein, and aggregation has been linked to neurotoxicity. Studies of synthetic peptides have contributed substantially to our understanding of the mechanism of aggregation, because the underlying biophysics of polyglutamine-mediated association can be probed independent of their context within a larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 51 publications
10
49
0
Order By: Relevance
“…Walters et al have shown in their experiments that while polyQ sequences of a shorter length and those of a longer length form fibers with clear bundles, the fiber morphology of the intermediate length peptides Q 26 shows a lateral alignment. 25 We see that this lateral alignment phenomenon is explained by the present simulations.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Walters et al have shown in their experiments that while polyQ sequences of a shorter length and those of a longer length form fibers with clear bundles, the fiber morphology of the intermediate length peptides Q 26 shows a lateral alignment. 25 We see that this lateral alignment phenomenon is explained by the present simulations.…”
Section: Resultssupporting
confidence: 75%
“…2225 Circular dichroism (CD) suggests that polyQ peptides are largely disordered and gives little hint of there being any difference between the short polyQ sequences and longer ones. 23,2628 The CD analysis suggests that Q 40 has about 10% α -helix content and only a trace amount of β -sheet and β -turn.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetics experiments initiated from fully disaggregated solutions that are supersaturated with respect to c s indicate the early formation of spherical aggregates, 10-30 nm in size, that are precursors of fibrillar aggregates. Fibril formation is barrierlimited and appears to proceed via nucleated conformational conversion within liquid-like spheres [82][83][84] in accord with the mechanism for crystallization that was proposed by ten Wolde and Frenkel. 85 In contrast, the formation of metastable liquidlike spheres does not involve discernible free energy barriers.…”
Section: Application Of Camelot For Simulations Of Block-copolymesupporting
confidence: 72%
“…These fibrils were identical in morphology to those observed previously for a similar Q-repeat peptide. 29 …”
Section: ■ Resultsmentioning
confidence: 99%